2016
DOI: 10.1007/s15007-016-1044-7
|View full text |Cite
|
Sign up to set email alerts
|

The red meat allergy syndrome in Sweden

Abstract: SummaryIn the last decade, a novel type of food allergy presenting with severe allergic reactions several hours a er consumption of red meat has been recognized.e allergic responses are due to IgE antibodies directed against the carbohydrate epitope galactose-α-1,3-galactose (α-Gal) found in mammalian meat.is review presents the red meat allergy syndrome in Sweden, discusses the features of the immune response to carbohydrates, and highlights the presence of heat stable α-Gal-containing proteins in meat.e numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…In this multicentre investigation on MA in Germany, 33 meat‐/innards‐allergic patients were included, and observations in clinical practice confirm that the prevalence is still increasing . ImmunoCAP ® analyses of meat‐allergic patients show that almost all patients (30/33) have elevated serum IgE against the α‐Gal‐containing antigen CTX (Tables and , Figure ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In this multicentre investigation on MA in Germany, 33 meat‐/innards‐allergic patients were included, and observations in clinical practice confirm that the prevalence is still increasing . ImmunoCAP ® analyses of meat‐allergic patients show that almost all patients (30/33) have elevated serum IgE against the α‐Gal‐containing antigen CTX (Tables and , Figure ).…”
Section: Discussionmentioning
confidence: 76%
“…Clinical reactions against the therapeutic monoclonal antibody cetuximab (CTX) used for cancer treatment are severe, sometimes even fatal, and are associated with IgE against galactosyl‐α‐(1,3)‐galactose (α‐Gal) . Meat allergy (MA) with particular clinical features was first observed in the USA and Australia and has also been investigated in Sweden, Italy, Austria, and Germany . It has been found that anti‐α‐Gal IgE plays a prominent role in MA and severe allergy symptoms that sometimes develop with a delay of several hours .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the evolutionary perspective, Neu5Gc has other consequences on human health . Despite the fact that humans lost the ability to synthesize Neu5Gc, small amounts can be found on human epithelial and endothelial cells .…”
Section: Neu5gc‐glycans Are Immunogenic In Humansmentioning
confidence: 99%
“…20 In this cold and arid region that straddles the Arctic Circle ticks are rare and there has been little report of mammalian meat allergy. 30,31 Of the 90 subjects who reported cat ownership, none had IgE to a-Gal (see Table E4 in this article's Online Repository at www.jacionline.org), and among the subjects in a cohort of 413 that was investigated, only a single subject (0.2%) had a level of IgE to a-Gal of at least 0.35 IU/mL.…”
Section: Further Evidence For a Connection With Tick Bitesmentioning
confidence: 99%